Sustainable Organic Waste Management through Black Soldier Fly (Hermetia illucens) Larvae Farming in Neglasari Village - Muhammad Syukur Sarfat; Muhammad Fauzan Al Fahrizi; Metha Anggina Ayudia; Muhammad Reyhan Alifya Akbar; Nisa Audina; Ahmad Fatoni; Fauzi Azmi; Della Oryza Febriana; Nurul Izzah Fasya; Siti Nurhaliza (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
The Maggot Farming Information Dissemination Program in Neglasari Village aimed to help community members understand how to manage organic waste through black soldier fly (BSF) (Hermetia illucens) farming and how to utilize BSF products, including larvae as high-protein animal feed and cultivation residue as organic fertilizer. This approach not only benefits the environment but also creates local economic opportunities. The program included theory sessions, hands-on maggot-farming practice, and interactive discussions on farming techniques and marketing strategies. It was conducted on January 12, 2025, at Saung Giwangkara River Tubing and was attended by 15 participants, including farmers and village youth. The program received a positive response, as evidenced by the formation of a maggot-farming group committed to independently developing this business. In addition to reducing organic waste, this initiative also provides a new source of high-nutrition animal feed. However, several challenges were identified, including limited pre-event promotion, which resulted in fewer participants at the beginning of the activity, and limited participant knowledge of marketing strategies. Despite these constraints, with stronger support from the village government and business partners, the program has the potential to develop into a sustainable enterprise. To ensure success, further technical guidance, improved access to funding, and the establishment of a village business unit or a maggot-farming cooperative are needed. These steps will help maximize the benefits of maggot farming for the people of Neglasari Village.